ChemInform Abstract: Preparation of Highly Photoluminescent CdTe Nanocrystals in a Mixing Alkali Medium. Issue 38 (September 2016) - Fang, Qunling; Zhang, Xiangyu; Xu, Huajian; Qian, Haisheng; Xuan, Shouhu
Abstract: Highly emissive thiol‐capped CdTe quantum dots (QDs) dispersed in H2 O are prepared via a mixed alkaline medium method employing thioglycolic acid or mercaptopropionic acid as thiol stabilizers and aqueous CdCl2 (pH 9, 10, or 12) to which 1 M NaOH or a mixture (1:2) of 30% NH3 and 1 M NaOH is dropwise added.